2014
DOI: 10.1002/ccr3.137
|View full text |Cite
|
Sign up to set email alerts
|

A successful early gore‐tex reconstruction of an abdominal wall defect in a neonate with Cantrell pentalogy: a case report and literature review

Abstract: Key Clinical MessageA surgical technique, materials used for abdominal wall reconstruction, and postoperative care are important for patient outcomes. We report the first case of neonate with Cantrell's pentalogy surviving early reconstruction of abdominal, diaphragmal and pericardial defects. Several recent investigations suggest that intraabdominal pressure monitoring may improve outcomes in this patient category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Abdominal wall defects are repaired by mobilization and gradually stretching of the abdominal muscles with the priority being to preserve intestinal blood flow and achieve a low-tension midline closure. Residual defects that cannot be closed primarily may be covered by the placement of a biocompatible or polytetrafluoroethylene (Gore-Tex) patch (37). The application of a sclerosing solution to promote formation of an amniotic sac eschar has been described in the conservative management of omphalocoeles, with plans to repair the resulting abdominal wall hernia at a later date (14).…”
Section: Initial Management and Surgical Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdominal wall defects are repaired by mobilization and gradually stretching of the abdominal muscles with the priority being to preserve intestinal blood flow and achieve a low-tension midline closure. Residual defects that cannot be closed primarily may be covered by the placement of a biocompatible or polytetrafluoroethylene (Gore-Tex) patch (37). The application of a sclerosing solution to promote formation of an amniotic sac eschar has been described in the conservative management of omphalocoeles, with plans to repair the resulting abdominal wall hernia at a later date (14).…”
Section: Initial Management and Surgical Repairmentioning
confidence: 99%
“…Although not routinely measured, the Pediatric Sub-Committee of the World Society of the Abdominal Compartment Syndrome recommended the use of intraabdominal pressure (IAP) monitoring in the critically-ill patient (38). Divkovic et al suggested that complication of increased IAP such as ventilator dependency, reherniation, and gut ischemia may be prevented by IAP monitoring in the neonatal intensive care unit (37). Clinical studies investigating a critical IAP level in neonates need to be undertaken and may guide further recommendations.…”
Section: Initial Management and Surgical Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of PC is 1:65,000 live births, with a 37% survival rate [ 4 ]. Surgical treatment should be performed at the earliest to prevent cardiac trauma; however, surgery depends on the size of the sternal defect, and the use of autologous tissues is preferable [ 5 ]. In this article, the authors present a case of PC diagnosed in the second trimester, focusing on the main ultrasound and fetal echocardiography findings as well as on delivery planning and surgical correction in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal wall defects (giant omphalocele and gastroschisis) and diaphragmatic hernia repair has historically seen the use of prosthetic patches of non-absorbable materials (Dacron, Polypropylene, Goretex, Goretex dual mesh with antibiotic) which represented a valid solution. However, they are not integrated in the surrounding tissues and can be a source of infection and complications in the medium–long term [1] , [2] , [3] . In the newborn, particularly in case of abdominal wall defects, the prosthesis is usually covered with very thin skin flaps, with poor representation of the subcutaneous tissue, increasing the risk of skin necrosis, infection and recurrence of the defect.…”
Section: Introductionmentioning
confidence: 99%